Study of reversible airway disease in patients with allergic rhinitis - Rao, Balabhaskar; B. J., Arun; Bhaskar, Vijay; Nagaraj, Niranjan (International Journal of Advances in Medicine, 2016)
Background: Allergy is a condition with wide spectrum of manifestations; it ranges from individuals with positive skin prick test without clinical features to allergic rhinitis, Atopic dermatitis, Asthma, Urticaria, Conjunctivitis, Enteritis and its most severe clinical manifestation Anaphylactic shock. This study aims to determine the baseline Spirometry in patients with allergic rhinitis using a computerized Spirometer. Assess the pulmonary function after inhalation of a bronchodilator to determine the degree of bronchodilator response. Correlate the clinical and laboratory parameters with the pulmonary functions. Methods: This study was conducted on 50 cases of allergic rhinitis presenting to our hospital from July 2006 to December 2007. Clinical diagnosis was made after a detailed clinical history and physical examination. All the patients included in the study underwent the following investigations: Complete hemogram, Absolute eosinophil count, X ray – chest and PNS, Serum total IgE level, spirometry. Results: Males constituted majority of population (62%) with mean age of 24±11.4 years. The most common symptom among allergic rhinitis patients was sneezing. Peripheral blood AEC levels were directly proportional to the severity of AR. Serum total IgE levels were also directly proportional to the severity of AR and severity of lower airway obstruction. PEF, FEF-25, FEF-50, FEV1% were significantly lower among AR patients with lower airway obstruction compared to patients with AR alone (p<0.05). Conclusions: Allergic rhinitis is a common disorder among general population predominantly involving the younger age group. Multicentric prospective studies are required to evaluate further, the role of spirometry among AR patients.